Methods for Detection and Quantification of Aflatoxins - Espinosa-Calderón, Alejandro; Contreras-Medina, Luis Miguel; Muñoz-Huerta, Rafael Francisco; Millán-Almaraz, Jesús Roberto; González, Ramón Gerardo Guevara; Torres-Pacheco, Irineo (IntechOpen, 2011)
None